1990
DOI: 10.1007/bf01857647
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of atrial natriuretic peptide during physical exercise in patients with congestive heart failure

Abstract: Plasma concentrations of atrial natriuretic peptide (ANP) were measured in 25 patients with organic heart disease during physical exercise (baseline and maximum workload) in order to investigate if the responsiveness of stimulated release of ANP is still preserved in patients with heart failure and chronically elevated cardiac filling pressures. Since plasma concentrations of ANP are known to be positively correlated with mean right atrial pressures (RAP), the patients were divided into two groups according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The elevated plasma ANP at rest combined with a significant increase during exercise found in the present study resembles the secretion pattern reported in exercise studies in patients with left ventricular dysfunction and CHF [22][23][24][25][26]. The mechanisms of exercise-induced increase in AF are probably similar to the mechanisms in patients with left ventricular dysfunction and CHF where Nishikimi et al [27] reported a positive correlation between pulmonary capillary wedge pressure and plasma ANP level during exercise, emphasizing the importance of left atrial pressure i.e.…”
Section: P=002supporting
confidence: 84%
“…The elevated plasma ANP at rest combined with a significant increase during exercise found in the present study resembles the secretion pattern reported in exercise studies in patients with left ventricular dysfunction and CHF [22][23][24][25][26]. The mechanisms of exercise-induced increase in AF are probably similar to the mechanisms in patients with left ventricular dysfunction and CHF where Nishikimi et al [27] reported a positive correlation between pulmonary capillary wedge pressure and plasma ANP level during exercise, emphasizing the importance of left atrial pressure i.e.…”
Section: P=002supporting
confidence: 84%
“…Several studies have shown that the plasma levels of ANP and BNP rise during dynamic exercise, not only in healthy subjects (18), but also in patients with some cardiac pathologies, such as atrial fibrillation (8), left ventricular dysfunction, and congestive heart failure (16,25). The enhanced synthesis and release of these potent vasodilating and natriuretic agents may represent an important factor for fluid regulation, preventing cardiac hypertrophy and leading to increased lipid mobilization, functions that may significantly help obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic exercise stimulates secretion of ANP in patients with CHF, and the increase in atrial pressure and stretching of the atrium are considered to be major stimuli for ANP secretion [6, 7]. The authors [8] and others [9–16] have evaluated plasma ANP response to exercise, and found that this response is augmented in patients with symptomatic CHF, and this augmentation is not present in patients with asymptomatic left ventricular dysfunction (LVD).…”
Section: Introductionmentioning
confidence: 99%